Strategi Pemasaran UMKM di Tengah Pandemi Covid-19 - Rahayu Setianingsih; Dwi Dewisri Kinasih; Ikhbal Akhmad; Rian Rahmat Ramadhan; Mohammad Kenjiro; Ghani Firja Anshari; Vyrna Risky Denita (ABDIMAS EKODIKSOSIORA: Jurnal Pengabdian Kepada Masyarakat Ekonomi, Pendidikan, dan Sosial Humaniora (e-ISSN: 2809-3917), 2021)
The spread of the Corona Virus in various countries has an economic impact that needs to be anticipated by all countries, including Indonesia. Government policies regarding social distancing and physical distancing at the beginning of the emergence of Covid 19 and followed by government policies regarding Social Restrictions In general, MSMEs face problems, especially related to marketing issues and coaching patterns which are felt to be not optimal during the COVID-19 pandemic. The method of implementing this community service activity is carried out with two implementation methods, namely theory exposure and experience sharing. Alternative marketing strategies that can be carried out by MSME actors, such as selling their products in e-commerce such as shopee, tokopedia, Bukalapak, gojek, grab and so on. MSME actors can also market their products on social media such as Facebook, Instagram, or in WhatsApp groups.